2013
DOI: 10.1016/j.cmet.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The IRP1-HIF-2α Axis Coordinates Iron and Oxygen Sensing with Erythropoiesis and Iron Absorption

Abstract: SUMMARY Red blood cell production is a finely tuned process that requires coordinated oxygen- and iron-dependent regulation of cell differentiation and iron metabolism. Here we show that translational regulation of HIF-2α synthesis by IRP1 is critical for controlling erythrocyte number. IRP1 null mice (Irp1−/−) display a marked transient polycythemia. HIF-2α mRNA is derepressed in kidney of Irp1−/− but not Irp2−/− mice leading to increased renal erythropoietin (Epo) mRNA and inappropriately elevated serum Epo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
166
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(176 citation statements)
references
References 38 publications
8
166
1
1
Order By: Relevance
“…1B). Although the two IRPs have considerable overlap in their binding specificities, each also has unique specificities (Henderson et al 1996;Anderson et al 2013). A further possibility for the discrepancy is that mutations to IRE B could be in some manner stimulating the endonuclease activity rather than inhibiting residual IRP interactions.…”
Section: Discussionmentioning
confidence: 99%
“…1B). Although the two IRPs have considerable overlap in their binding specificities, each also has unique specificities (Henderson et al 1996;Anderson et al 2013). A further possibility for the discrepancy is that mutations to IRE B could be in some manner stimulating the endonuclease activity rather than inhibiting residual IRP interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Irp1 −/− mice exhibit features of Hif2a overexpression and hyperproduction of Epo, while Irp1 constitutive transgenic mice show defects in erythroid differentiation that can be attributed to decreased Hif2a expression. [113][114][115] These observations indicate that Irp1 acts as an iron and oxygen sensor, linking iron metabolism with erythropoiesis via EPO. In iron deficiency, Irp1 suppresses HIF2a and Epo expression to reduced iron availability, consistently with iron-restricted erythropoiesis.…”
mentioning
confidence: 92%
“…44 While this manuscript was in preparation, erythropoietic abnormalities of IRP1 2/2 mice were also reported by others. 45,46 Ghosh et al 45 further showed that IRP1 2/2 mice develop pulmonary hypertension, an additional pathology shared by Chuvash polycythemia patients 47 and the respective mouse model. 48 Together, the data reported here and elsewhere 45,46 highlight the crucial role of IRP1 as an upstream regulator of erythropoiesis and systemic iron metabolism.…”
Section: 39mentioning
confidence: 99%